Pengaruh Aromaterapi Lemon Terhadap Frekuensi Penurunan Mual Muntah pada Ibu Hamiltrimester I di RSUD Aek Kanopan Kecamatan Kualuh Selatan Kabupaten Labuhan Batu Utara Tahun 2024 - Vibriani Siregar; Dessy Ratna Sari; Ninsah Mandala Putri Sembiring; Ariska Fauziyanti; Zulkarnain Batubara (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Nausea and vomiting are symptoms that a reasonable and often happen in the first trimester of pregnancy. It usually occurs in the morning, but can occurs at any time including at night. This condition can cause dehydration or lack of fluid and electrolyte inbalance, hence the condition of pregnant mother's get worse. Lemon aromatherapy is one of alternative method to decrease nausea and vomiting in the first trimester of pregnancy. It provides relaxation and sedative by stimulating the limbic system. This study was conducted to find the effect of lemon aromatherapy to decrease nausea and vomiting in the first trimester of pregnancy. Design used in this study was pre-experiment (one-group pretest-posttest designed). The population were all pregnant women that have nausea and vomiting in the first trimester of pregnancy. The samples were 12 respondent taken by purposive sampling according to the inclusion criteria. The independent variable was lemon aromatherapy. While the dependent variables were nausea and vomiting in the first trimester of pregnancy. Data were collected using structured questionnaire and observation. Data were then analyzed using statistic test (wilcoxon signed rank test) with level of significance α≤0.05.